Model Checking Unbounded Artifact-Centric Systems - Lomuscio,AR; Michaliszyn,J (AAAI Press, 2014)
Artifact-centric systems are a recent paradigm for represent-ing and implementing business processes. We present furtherresults on the verification problem of artifact-centric systemsspecified by means of FO-CTL specifications. While the gen-eral problem is known to be undecidable, results in the lit-erature prove decidability for artifact systems with infinitedomains under boundedness and conditions such as unifor-mity. We here follow a different approach and investigate thegeneral case with infinite domains. We show decidability ofthe model checking problem for the class of artifact-centricsystems whose database schemas consist of a single unaryrelation, and we show that that the problem is undecidable ifartifact systems are defined by using one binary relation ortwo unary relations.